Mixed Acinar-Neuroendocrine Carcinoma of the Pancreas with Neuroendocrine Predominance - Onyekachi Henry Ogbonna; Marie Carmel Garcon; Kostas N. Syrigos; Muhammad Wasif Saif (Case Reports in Medicine)
Background. Pancreatic tumors are rare and could arise from either the exocrine (ductal and acinar cells) or the endocrine (neuroendocrine cells) components of the pancreas. In some instances, the occurrence of pancreatic tumors comprising both acinar cells and neuroendocrine cells, with neuroendocrine cells making up more than 30% of the tumor, has been identified. This unique entity has been referred to as mixed acinar-neuroendocrine carcinoma (MANEC). Only about 20 such cases have been reported in the literature. Case Report. We report an interesting case of MANEC with neuroendocrine cell predominance in a woman presenting with epigastric pain secondary to a pancreatic mass with acinar and endocrine differentiation. She underwent surgical resection of the tumor and was offered adjuvant treatment chemotherapy with carboplatin, etoposide, and radiotherapy for positive tumor resection margins. Conclusions. Given the paucity of the cases of MANEC, continuous reporting of these cases when identified should be encouraged to aid oncologists in understanding the disease and help establish standardized management.